DEVELOPMENT OF THE CHP-THERMAL SCHEMES IN CONTEXTS OF THE CONSOLIDATED ENERGY SYSTEM OF BELARUS - V. N. Romaniuk; A. A. Bobich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper deals with the structural specifics of the Belarus Consolidated Energy System capacities in view of their ongoing transfer to the combined-cycle technology, building the nuclear power plant and necessity for the generating capacity regulation in compliance with the load diagram. With the country’s economic complex energy utilization pattern being preserved, the generating capacities are subject to restructuring and the CHP characteristics undergo enhancement inter alia a well-known increase of the specific electricity production based on the heat consumption. Because of this the steam-turbine condensation units which are the traditional capacity regulators for the energy systems with heat power plants dominance are being pushed out of operation. In consequence of this complex of changes the issue of load diagram provision gains momentum which in evidence is relevant to the Consolidated Energy System of Belarus. One of the ways to alleviate acuteness of the problem could be the specific electric energy production cut on the CHP heat consumption with preserving the heat loads and without their handover to the heat generating capacities of direct combustion i.e. without fuel over-burning. The solution lies in integrating the absorption bromous-lithium heat pump units into the CHP thermal scheme. Through their agency low-temperature heat streams of the generator cooling, the lubrication and condensation heat-extraction of steam minimal passing to the condenser systems are utilized. As a case study the authors choose one of the CHPs in the conditions of which the corresponding employment of the said pumps leads to diminution of the fuel-equivalent specific flow-rate by 20−25 g for 1 kW⋅h production and conjoined electric energy generation capacity lowering. The latter will be handed over to other generating capacities, and the choice of them affects economic expediency of the absorption bromous-lithium heat pump-units installation decision.